THE EFFECT OF EUCALYPTUS (MELALEUCA CAJUPUTI) FORESTRY PROGRAM ON INCREASING INCOME OF FOREST FARMERS IN GUNUNG KIDUL REGENCY SPECIAL REGION OF YOGYAKARTA - Bayu Mahendra (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Forests play an important role in terms of poverty alleviation, increasing welfare and providing additional income. Forests in Indonesia can be cultivated for farmers on the basis of social forestry programs. The Special Region of Yogyakarta has a forest area of ​​around 19,030ha with the proportion of 15,711.70ha being production forest and 4,318.80ha being protected forest. Community income derived from forests is very fluctuating so that a suitable program is needed to be implemented. This study aims to analyze the increase incomeof forest farmers participating in the Eucalyptus forestry program. The number of respondents collected was 74 forest farmers and interviews and observations were carried out to obtain detailed results. The next test is the t test, which compares the average income between eucalyptus forest farmers and non-eucalyptus forest farmers. The average beetween in the income of forest farmers with and without eucalyptus is 24%. The results of the t test show that the value of Sig. shows the number 0.000 or <0.005 so that it can be said that the difference in income between forest farmers with eucalyptus and forest farmers without eucalyptus is significant.